Antioxidant activities of Melastoma malabathricum Linn. leaves - Abdullah, Adnin; Mat So'ad, Siti Zaiton (2018)
Melastoma malabathricum L. (M. malabathricum L.) is a traditional herb that is included in the family of Melastomataceae, it being so attractive with dark – purple magenta flowers and fruits like berries. It possessed many potential pharmacological activities such as anti-inflammatory, anti-bacterial, anti-oxidant and gastroprotective activity. This study were aimed to extract M. malabathricum L. leaves using ethyl acetate and methanol. Then, it was to determine the antioxidant activities of M. malabathricum L. and last objective was to separate compounds from M. malabathricum L. leaves extracts using Thin Layer Chromatography (TLC). Extraction were done with two different solvents which were ethyl acetate and methanol. Then the anti-oxidant activity for both ethyl acetate and methanol extract were tested using DPPH (2,2-diphenyl-1-picrylhydrazyl) method. The IC50 calculated were compared with ascorbic acid as control. Then, for TLC test, there were 3 solvent systems used which were 90% chloroform and 10% methanol, 80% chloroform and 20% methanol and 95% ethyl acetate and 5% methanol. Results illustrated that, ethyl acetate extract showed higher anti-oxidant activity compared to methanol extract in which the IC50 were 8.61 µg/mL and 27.37 µg/mL respectively. The IC50 for control was 3.02 µg/mL. Next, for TLC, the solvent system with 90% chloroform and 10% methanol was the best among all the systems. This plant had a big potential as anti-oxidant in future. Then, there were few compounds with different polarity spotted which indicated that variety of compounds that ranged from highest to lowest polarity available in the extracts.